Karang Taruna Human Resource Competency Development Through Soft Skills and Digital Literacy Training in Pematang Johar Village - Lisa Elianti Nasution; Phan Bao Giang; Sipnarong Kanchanawongpaisan; Muhammad Hafiz Abd.Rashid; Hendra Halim; Khoirul Amri; Dedi Irawan (Eastasouth Institute, 2025)
This community service program was carried out to answer the issue of lack of soft skills and digital literacy competencies among members of the Pematang Johar Village Youth Organization, which has an impact on the suboptimal role of youth in social activities and village development. The focus of this service is to increase communication capacity, leadership, teamwork, and the ability to utilize digital technology. The activity aims to empower youth through strengthening personal and organizational competencies. The methods used are participatory action research (PAR) and practice-based participatory training, which are carried out through soft skills sessions, basic digital literacy, advanced digital literacy, and technical assistance. The results of the activity showed a significant increase in the communication skills, leadership, and digital skills of the participants, the formation of a digital creative team, and the improvement of the organizational culture of Karang Taruna. This program has succeeded in encouraging youth as agents of social change in the village.